Убийца поневоле: повести / Александра Маринина - Маринина Александра Борисовна (Ард ЛТД, 1997)
Экземпляры: ф.15 (2004) / Инвентарный номер: 39601 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44